Assessment of Nurses knowledge toward prevention of Complications related Valvular Replacement Surgery at Surgical Department in AL-Nasiriyah Heart Center - abbas, Douaa; jasim, aqeel (Iraqi National Journal of Nursing Specialties, 2019)
Objectives: The study aims to assess  the nurses knowledge toward prevention of complications related to valvular  replacement surgery and to find out the relationship between nurses knowledge and their demographic and occupational characteristic's Which as (Age, gender, level of education ,years of experience in Surgical Department , and training sessions) Methodology: A descriptive design  (a cross-sectional study ) was carried out from December 2017 to May 2018 in order to assess nurses' knowledge of preventing complications Valvular Replacement Surgery at Surgical Department in  Nasiriyah Heart Center on a purposive (non-probability) sample was used in this study that composed  of (70) nurses of the morning and night shifts. Data were collected by using the technique of   self-report questionnaire which designed and constructed by the researchers  from previous related studies and consisted of two Part one included  ' socio-demographic characteristics for   the   nurses, Part two : knowledge items related to anatomy ,  physiology heart valve , heart valve replacement and complication heart  valve replacement. and nursing care . The validity of the questionnaire was determined by presenting the questionnaire to (13) specialized experts. The reliability of the internal consistency was achieved by applying the alpha correlation Coefficient (r=0.85) which was statistically acceptable. The data were analyzed by applying descriptive and inferential statistics .Results: The results showed that most of the participants in the research of nurses  at  age group (20-29) years, and the study revealed that the nurses have a moderate knowledge towards the prevention of complications of valve replacement surgery by significant  level among  all  items of  the scale. The study concluded that most nurses did not have sufficient experience in work in the surgical department and most of them did not train well . Recommendations: The study recommended spreading awareness among nurses regarding the prevention of complications of valves replacement surgery through instructional sessions and continuing education lectures  to increase awareness of nurse's in ways of preventing complications of heart valve replacement.